2002
DOI: 10.1023/a:1021488222243
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The eects of temperature and microwave frequency on the dielectric properties of MoS 2 and Pt catalysts together with an aluminum oxide support were investigated. Dielectric constants and dielectric loss factors were measured in a temperature range of 200±800 8C by a cavity resonator technique with a cylindrical copper cavity resonating in TM 0n0 modes (n 1; 2; . . . ; 5), which corresponded to frequencies of 0.615, 1.413, 2.216, 3.020, and 3.825 GHz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…It can be seen that, in general, the absorbed power increased with temperature rising and the increase in power tended to be smaller at higher temperatures indicating an increase in microwave heating efficiency. This is in agreement with the previous study where the dielectric loss of the catalyst generally increased with increasing temperature [22,23].…”
Section: Microwave Power Absorptionsupporting
confidence: 93%
See 1 more Smart Citation
“…It can be seen that, in general, the absorbed power increased with temperature rising and the increase in power tended to be smaller at higher temperatures indicating an increase in microwave heating efficiency. This is in agreement with the previous study where the dielectric loss of the catalyst generally increased with increasing temperature [22,23].…”
Section: Microwave Power Absorptionsupporting
confidence: 93%
“…It has been demonstrated that the power absorbed by a dielectric is determined by a combination of the electromagnetic field applied, the volume of the sample and the dielectric property [11,22,23]. Furthermore, it has been shown that in the identical reactor system small changes in the dielectric loss characteristics of the catalyst can result in significant differences in the temperature gradient established within the catalyst [22].…”
Section: Comparison Of Catalysts Heated In Gas Mixtures With and Withmentioning
confidence: 99%
“…Furthermore, it has been found that these parameters are both temperature and radiation frequency dependent [57]. Some effort has been made to quantify the effects of temperature and microwave frequency on dielectric properties [52,58] in view of the fact that few data are available on the temperature variation of dielectric properties, particularly for heterogeneous catalysts in an elevated temperature range.…”
Section: Temperature and Frequency Dependency Of Dielectric Propertiementioning
confidence: 99%
“…Data for both catalyst supported on c-Al 2 O 3 and for bulk MoS 2 are also included for comparison. Based on these measurements, a model for the energy dissipation factor or loss tangent as a function of temperature has been proposed [52] …”
Section: Temperature and Frequency Dependency Of Dielectric Propertiementioning
confidence: 99%
See 1 more Smart Citation